(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the phenomena of literality and implication, which are considered an important terminological unit of pragmalinguistics, one of the new areas of linguistics. Also, the methodological and functional study of the phenomenon of subtext took into account the presence of scientific approaches based on different points of view, the diversity of the classification principle. The theoretical foundations of the research and methods of its implementation are presented in detail. Methods such as comparison, contradiction, semantic and pragmatic analysis, generalization as a universal method were used in the work. The phenomenon of subtext is reduced to analysis as an element of implication that has a hidden judgment. With the help of linguistic evidence obtained from fiction, the types of subtext are clearly identified.